EVALUASI MULTI-KRITERIA KERUANGAN UNTUK PENILAIAN RISIKO TOTAL TSUNAMI DI PACITAN - , Muhammad Wahyu Dicky Zulkarnain; Dr. Sunarto, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pacitan is an area on the southern island of Java in the form of the bay and dealing directly with the Indian Ocean. The basis of the Indian Ocean is an area of active earthquake that potentially create tsunami. Gulf Pacitan never experienced an earthquake and tsunami in 1818, 1840, 1859, 1883, 1904, 1921, 1925, 1957, 1994, and 2006 based on historical earthquake and tsunami data the southern ocean. This study aims to analyze spatial multi-criteria evaluation (SMCE) for a total risk assessment of tsunami in Pacitan. Tsunami risk assessment by semi-quantitative method, to construct the risk index value between 0 and 1. Tsunami hazard using the model adopted from Pacitan tsunami run-up of Mardiatno at 2008. Judging the risk of using the physical, social and economic parameters as a component of total tsunami vulnerability. Physical vulnerability is obtained through a survey based on the vulnerability of buildings PTVA-3. Parameters of health, disaster preparedness, and working population used to build the total tsunami coping capacity. Weighting parameters using pairwise comparation method and ranking summary. The total risk value of tsunami Pacitan resulted from spatial multi-criteria evaluation range from 0.23 to 0.81. Total risk of tsunami Pacitan dominated high and very high levels. Characteristics of Pacitan total risk tsunami high at Ploso village and the area around the River Gridulu. The highest total risk of a tsunami in the Ploso village